Analisis Intensitas Cahaya terhadap Voc dan Isc Panel Surya - Enggar Hero Istoto; Ilham Faqih; Mura Shaki; Sasha Avrilia; Juliadi Zalukhu (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Due to Indonesia's year-round abundance of sunlight, solar energy is one of the renewable energy sources with substantial development potential. Photovoltaic panel output characteristics, particularly open circuit voltage (Voc) and short circuit current (Isc), are impacted by variations in solar irradiation. The purpose of this study is to examine how solar irradiation affects a 50 WP monocrystalline solar panel's Voc and Isc values. Direct measurements were made every five minutes between 10:00 and 11:30 in the morning as part of an experimental approach. Solar irradiance, open circuit voltage, and short circuit current were among the parameters that were measured. The results showed that increasing irradiance significantly affected the Isc value, while Voc tended to remain relatively stable. The highest irradiance value was 982 W/m² with a Voc value of 20.6 V and an Isc value of 3.21 A. The findings indicate that the output current of the photovoltaic panel is more sensitive to irradiance changes than the output voltage